Implementation of the Family Hope Program (PKH) in Sidomulyo Village, Stabat District Langkat Regency - Sari, Cici Indah; Hartono, Budi; Lubis, Maksum Syahri (Formosa Journal of Social Sciences (FJSS), 2024)
Implementation is a concrete step in realizing various policies and regulations that have been well structured. The Family Hope Program is the government's effort to alleviate poverty by the Law on poverty alleviation. Social minister no. 1 of 2018 states that the PKH program was prepared with the aim of reducing poverty rates and breaking the chain of poverty, improving the quality of human resources, and changing the behavior of KPMs which are relatively less supportive of increasing welfare. Implementation of the family hope program in the Sidomulyo sub-district, Staba sub-district is the focus of research in this paper. This research aims to analyze how the Family Hope Program (PKH) is implemented in Sidomulyo subdistrict, Stabat subdistrict, and to analyze the factors that influence the Family Hope Program (PKH) in Sidomulyo subdistrict, Stabat subdistrict, Langkat district. This research uses a descriptive method with a qualitative approach using interview techniques with key, main, and additional informants. The research object is the PKH beneficiary family, Sidomulyo sub-district, Stabat sub-district, Langkat district